Effects of Different Levels of Restraint Stress on Bone-Implant Contact - Bozoglan, Alihan; Dundar, Serkan; Yildirim, Tuba T.; Bulmus, Ozgur; Ertugrul, Abdullah Seckin; Bozoglan, Merve Y.; Toy, Vesile Elif (Lippincott Williams & Wilkins, 2019)
This study examined the effects of different levels of chronic restraint stress on bone-titanium implant contact in rats. This study included 32 adult female Sprague-Dawley rats. The machined surface titanium implants were surgically placed into the metaphyseal region of the rat tibias. Next, the rats were divided randomly into 4 groups, namely, control (CNT) (n = 8), low-restraint stress (LRS) (n = 8), medium-restraint stress (MRS) (n = 8), and high-restraint stress (HRS) (n = 8) groups. The rats in the CNT group received only the titanium implants surgically but did not receive any further treatment during the experimental period of 30 days. The rats in the LRS, MRS, and HRS groups were applied restraint stress for 1, 2, and 4 hours, respectively, daily for 28 days starting from day 2 after the surgery. At the end of the study period, the rats were sacrificed and their implants and the surrounding bone tissues were harvested for performing non-decalcified histological analysis. Moreover, blood samples were collected from the rats and were centrifuged for analyzing serum cortisol levels. Serum cortisol levels of the rats in the LRS, MRS, and HRS groups were higher than those of the rats in the CNT group (P<0.05). Moreover, serum cortisol levels of the rats in the HRS group were higher than those of the rats in the MRS and LRS groups (P<0.05). The extent of bone-implant contact was lower in the rats in the HRS group than in the rats in the CNT and LRS groups (P<0.05). These data suggest that the application of 4-hour chronic restraint stress during the 28-day experimental period impaired the bone-implant contact.
23rd International Scientific Dental Congress of the Turkish-Dental-Association -- SEP 21-24, 2017 -- Istanbul, TURKEY
Keywords: Bone-implant connection; cortisol; osseointegration; rat; restraint stress level